Enforcement and Environmental Compliance: A Statistical Analysis of the Pulp and Paper Industry - Jay P. Shimshack
This paper explores empirically the impact of changes of enforcement efforts on environmental compliance. Our strategy is to link observed fines and other enforcement actions to subsequent compliance behavior. We find that, on the margin, the impact of a fine for water pollutant violations is about a two-thirds reduction in the statewide violation rate in the year following a fine. This surprisingly large result obtains through the regulator’s enhanced reputation. We find that the deterrence impact on other firms in a state is almost as strong as the impact on the sanctioned firm. In contrast to fines, non-monetary sanctions contribute no detected impact on compliance.Fines, Reputation, Pollution, Compliance, Enforcement